Deforestation survey in the Brazilian Pantanal in 1990/91 - Silva, João dos Santos Vila da; Abdon, Myrian de Moura; Silva, Marta Pereira da; Romero, Hilda Ribeiro (Pesquisa Agropecuaria Brasileira, 1998)
This work involved an area of 138,183 km2 relative to the Brazilian Pantanal wetlands, aiming to map and quantify deforested areas up to 1990/91, on a 1:250,000 scale. The research was carried out through interpretation of satellite images, field observations (terrestrial and aerial), and use of two Geographic Information Systems (GIS) and Global Positioning System (GPS). Visual interpretation of coloured composition (3B, 4G, 5R) TM-Landsat images on a 1:250,000 scale, of the year 1990/91, was performed. The areas of typical patterns of deforestation and areas where native vegetation was replaced by exotic vegetation were extracted from those interpretations. Oblique 35 mm photographs were taken to check that information, while on the ground the visited areas were photographed, positioned bye GPS, identified and recorded on working maps and images. At the end of the project the municipal maps of the 16 counties of the Pantanal, containing plain/upland delimitation and deforestation patches on the plain, were ellaborated. These information were stored and manipulated on GIS (GIS-INPE and SPRING). The deforested area in the Pantanal in 1990/91 was quantified as 5,437.73 km2 or 3.9% of the Pantanal area.
Keywords: remote sensing; Geographic Information System